Stability of Nuclei - Mallik, Arbind Kumar (Himalayan Physics, 2011)
Nucleus is composed of uncharged neutrons and charged protons, chiefly given the fact that the electrostatic repulsion of the protons tends to disrupt the nucleus? What is the nature of forces that ensure stability between charged and uncharged particles in the nucleus? Attempts have been made to solve this problem both on the experimental and theoretical sides. In this article, a brief statement of these investigations is described. Search for the causes of stability of nuclei have been made in the following four directions, Relative abundance of elements as well as of isotopes that occur in nature, the binding energy per nucleon curve, Decay constant of natural radioactive substances, Magic numbers. Keywords: Uncharged neutrons; Charged and uncharged particles; Nuclei The Himalayan Physics Vol.2, No.2, May, 2011 Page: 61-64 Uploaded Date: 1 August, 2011